The Sacrificial Life and Death of the Servant (Isaiah 52:13-53:12) - Blenkinsopp, Joseph (Vetus Testamentum, 2016)
The argument presented in this article is that the term ‘asham’ in Isa 53:10 refers to the sacrificial ritual of the guilt offering, that this reference is supported by indications throughout Isaiah 53, and that therefore the suffering and death of this Servant of the lord is to be understood as sacrificial by analogy with the ritual of the guilt or reparation offering in the book of Leviticus. This conclusion, much contested in contemporary scholarship, is supported by a survey of the reception of this text in the period prior to early Christianity.